Effect of Population Density and Altitude on COVID-19 : A Spatial Pattern - Cahyati, Widya Hary; Purwoko, Sidiq; Farida, Eko; Khairunnisa, Marizka; Asturiningtyas, Ika Puspita; Ashar, Hadi; Puspitasari, Candra (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
The Covid-19 pandemic that has been going on since March 2020 has spread rapidly, with high mortality In Indonesia. Central Java, Covid-19 remains a disease with a Case Fatality Rate (CFR) of 4.4% and is above Indonesia’s CFR of 3.0%. In Magelang itself, positive cases of Covid-19 in 2020 reached 4418 and were among the top 3 cases in Central Java Province. This study’s purpose was to spatially describe the distribution of new cases of Covid-19 in terms of population density and elevation of the sub-district area in Magelang. The type of research is descriptive quantitative with ecological studies using a spatial approach. The results showed that the distribution of new cases of Covid-19 has a unique pattern in mapping based on population density and altitude. Some of the new distribution cases showed a distribution pattern following the regional elevation and almost entirely following the pattern of population density. The increase of Covid-19 tends to be higher in areas with high-density populations and low-altitude regions. This study concludes that the distribution pattern of new Covid-19 cases is influenced by population density and the area’s height during the peak period of new Covid-19 cases in 2020 at Magelang.